Academic cooperation for development of agribusiness engineering - Ramírez-López, Pedro Martín (2012)
This article tries to explain the contents and results of all operations in two research projects of the Spanish Agency for International Development (here in after AECID). Those acade- mic achievements have produced concrete results at the level of small producers, the preparation of teachers of both universities and the training of stu- dents. By collecting this information makes clear that the new opportunities offered by PCI-AECID projects give a boost to the rural areas, impor- tant spaces of socio-economic and organizational development to increase their levels of economic participation, social, cultural and political and conse- quently, their standard of living.